Reconstruction of facial soft tissue: comparison between conventional procedures and the facelift technique. Issue 9 (November 2016) - Bartella, A.K.; Ghassemi, M.; Hölzle, F.; Ghassemi, A.
Abstract: We compared the result of replacement using a modified facelift technique with those of other commonly used surgical techniques for the treatment of defects of the soft tissue of the infraorbital and cheek region. We made a retrospective observational study of 86 patients who had defects of the facial soft tissue after excision of malignant tumours. Procedures used for reconstructions included non-vascularised skin grafts, local flaps, facelift technique, and microvascular free flaps, and we evaluated morbidity; duration of hospital stay; the need for, and duration of stay in the intensive care unit (ICU); and functional and aesthetic outcomes. We studied 46 men and 40 women (mean (range) age 71 (8-99) years). We found no significant difference between the methods apart from shorter duration of hospital stay and lower incidence of ectropion in the facelift group. The facelift technique also gave the best aesthetic outcome. However, in defects larger than 60 cm 2, microvascular free tissue transfer was the only choice. The facelift technique is reliable and safe, and gives excellent aesthetic and functional outcomes, but its use is limited to defects smaller than 60 cm 2 .